NIST PQC: Code-Based Cryptosystems - Kuznetsov, А.А.; Gorbenko, Yu.I.; Lutsenko, М.S.; Prokopovych-Tkachenko, D.I.; Pastukhov, M.V. (Radiotekhnika, 2018)
The code-based schemes, which were submitted to the contest of post-quantum crypto algorithms NIST PQC, are studied in this work. The general characteristics of the algorithms are explored and basic properties and parameters are estimated. A comparative analysis of the electronic digital signature schemes, public-key cryptosystems and key encapsulation schemes are carried out according to the criteria of speed and length of the main cryptographic parameters.